2013
DOI: 10.1530/erc-12-0281
|View full text |Cite
|
Sign up to set email alerts
|

Transrepression of the estrogen receptor promoter by calcitriol in human breast cancer cells via two negative vitamin D response elements

Abstract: Calcitriol (1,25-dihydroxyvitamin D 3 ), the hormonally active metabolite of vitamin D, exerts its anti-proliferative activity in breast cancer (BCa) cells by multiple mechanisms including the downregulation of the expression of estrogen receptor a (ER). We analyzed an w3.5 kb ER promoter sequence and demonstrated the presence of two potential negative vitamin D response elements (nVDREs), a newly identified putative nVDRE upstream at K2488 to K2473 bp (distal nVDRE) and a previously published sequence (proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Calcitriol has also been shown to modulate the transcription by interacting with either the positive or negative VD response element (VDRE) of the promoters of target genes [11]. For example, VDR agonists were previously reported to down-regulate the expression of estrogen receptor (ER) α, which has two potential negative VDREs in the promoter, through a VDR-dependent mechanism in ER-negative breast cancer cells [12,13]. A genome-wide investigation by RNA-Seq technology and The Cancer Genome Atlas identified the transcriptional targets of calcitriol in breast cancer cells [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Calcitriol has also been shown to modulate the transcription by interacting with either the positive or negative VD response element (VDRE) of the promoters of target genes [11]. For example, VDR agonists were previously reported to down-regulate the expression of estrogen receptor (ER) α, which has two potential negative VDREs in the promoter, through a VDR-dependent mechanism in ER-negative breast cancer cells [12,13]. A genome-wide investigation by RNA-Seq technology and The Cancer Genome Atlas identified the transcriptional targets of calcitriol in breast cancer cells [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 1α,25-dihydroxyvitamin D 3 and analogs have been reported to alter sex hormone signaling by suppressing the expression of estrogen receptor α [72][73][74][75][76][77] . It has also been reported that vitamin D deficiency alters reproductive functions in both male and female rats, indicating that vitamin D may affect sex hormone signaling 78,79 .…”
mentioning
confidence: 99%
“…This example very nicely demonstrates that application of formal criteria without overall weight of evidence assessment might result in misinterpretations. The effects on aromatase activity expression have been observed in breast cancer cells in vitro [37,39,40] and in immunocompromised mice bearing MCF-7 xenografts [41]. The latter study was not regarded for the classification due to the artificial situation generated in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the interaction with the parathormone system the Vit-D3 metabolite 1,25-Dihydroxyvitamin D3 has been shown to act as selective aromatase modulator, decreasing aromatase expression in breast cancer cells and the breast adipose tissue surrounding a breast tumour, resulting in a reduction of the local production of estrogens within the breast. Additionally, 1,25-dihydroxyvitamin D3 also represses estrogen receptor expression in breast cancer cells in vitro, two mechanisms possibly relevant for breast cancer therapy [37]. For the sake of this screening activity this publication was taken as in vitro evidence for an EATS-mediated MoA.…”
Section: -14]mentioning
confidence: 99%